Flypaper Effect pada Dana Alokasi Umum, Dana Bagi Hasil, dan Pendapatan Asli Daerah terhadap Belanja Daerah pada Provinsi di Indonesia - Hadi Sasana (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
Fiscal decentralization and implementation of local autonomy are expected to improve equality of local developments, in accordance with the motivation of local governments to develop their region based on their specific potentiality. However, some researches indicate that although decentralization has been implemented in Indonesia for almost a decade, the regions still strongly depend on the central government financially. This research examine the fly paper effect as one of the indicators of the success of decentralization. By examining all provinces in Indonesia, the research try to find out (1) whether the general allocation fund,revenue-sharing, and regionally original income influence the regions’ spending; (2) whether there has been a fly paper effect. The important findings of this research indicate that all provinces although have high regionally original income, experienced the flypaper effect. Keywords: DAU, DBH, flypaper effect, PAD